If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 = 3t + -23 Reorder the terms: 19 = -23 + 3t Solving 19 = -23 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 19 + -3t = -23 + 3t + -3t Combine like terms: 3t + -3t = 0 19 + -3t = -23 + 0 19 + -3t = -23 Add '-19' to each side of the equation. 19 + -19 + -3t = -23 + -19 Combine like terms: 19 + -19 = 0 0 + -3t = -23 + -19 -3t = -23 + -19 Combine like terms: -23 + -19 = -42 -3t = -42 Divide each side by '-3'. t = 14 Simplifying t = 14
| 3(3m+4)-2(m-7)=0 | | 6d-18+2=2 | | 24/.04 | | 12x+12x+16+10x-4=102 | | -20=-4q | | b^3+15b^2-904=0 | | -10t=90 | | 0.4/24 | | [7-2y]-8=-3 | | 2x^2-22x-12=0 | | -2[d+6]=-10 | | (-15)(-17)= | | x/5=x/3-2 | | -8x+2+5x=-13 | | 6x-(3x-8)=29 | | -6+-8g=-62 | | b^3+b^2+1=0 | | 5=d+6 | | -80=8(b-5)-10(b+6) | | 10k^2-24=-12k | | -18-4a=-2 | | 20x+5x+1=101 | | x-9/10=21/10 | | (2y-5)/(6x-7y)=x | | 42-53+(-34)-56= | | Cos(3.14+6)=0 | | w/6*30 | | 42x-5=-20 | | 3x-(2-x)=x-2(x+3) | | -7-7(1-8x)=-126 | | 4x-2=7+(4x-9) | | 3/4x-6=0 |